The reception of Ciotka’s works in the first half of the 20th century and the question of attribution of the poem «Mužyckaja dola» - Zaprudski, Igor N.; Korchashkina, Daria V. (Journal of the Belarusian State University. Philology, 2020)
The article is devoted to the study of the reception of the work of Aloiza Pashkevich (Ciotka) (1876–1916), the rooting of ratings and her establishment in the literary process. The object of study are the publications of critics and theorists of literature dedicated to Ciotka for the period 1918 to 1950. The subject is the problems of interpretation of the literary and journalistic texts of the writer, the features of the preparation and publication of collections of her works for the specified period, as well as the issue of attribution of the poem «Mužyckaja dola». Have been introduced into scientific use and archival materials were used, that’s help to shed light on the circumstances of the preparation and publication of the posthumous collection of Ciotka.
Keywords: reception; attribution; literature process; revolutionary pathos; biographical method; psychoideology; vulgar socialism